UPAYA MENINGKATKAN KEMAMPUAN KOMUNIKASI ORAL SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION SISWA KELAS VII-A SMP NEGERI 22 SURAKARTA TAHUN PELAJARAN 2012/2013 - Wahyudi, Wahyudi; Widoretno, Sri; Sugiharto, Bowo (BIO-PEDAGOGI, 2015)
The purpose of the research is for increasing students oral communication skills through the implementation of Problem Based Instruction learning model.This research is classroom action research that is doing by 2 cycle, each consist of 4 phase that  is planning, acting, observing, and reflecting. Data that resulted from this research are students oral communication skills that gained by observation and  supported by the result of  interview, documentation, and cognitive test. Resource of data are from observation paper, information from the result of  students and teacher interview, observation note, and learning material that are silaby, lesson plan, and students worksheet. Data collection is through the observation, interview, and documentation. Data validity is test by method triangulation. Data analysis is done by qualitative descriptive technique. Result in this research is showed that students oral communication skills generally increased in the each cyle. Score performance of answering teacher questions indicator are 9,09% on pracycle; 30,30% on 1st cycle; and 45,45% on 2nd cycle. Score performance of ask about related topic indicator are 3,03% on pracycle; 0% on 1st cycle; and 27,27% on 2nd cycle. Score performance of give an opinion on the class disscussion indicator are 0% on pracycle; 3,03% on 1st cycle; and 15,15% on 2nd cycle. Score performance of give an opinion on the group disscussion indicator are 3,03% on pracycle; 60,61% on 1st cycle; and 54,55% on 2nd cycle. Score performance of capability in organizing material indicator are 0% on pracycle; 69,70% on 1st cycle; and 60,61% on 2nd cycle. Score performance of using appropriate language indicator are 0% on pracycle; 51,52% on 1st cycle; and 52,52% on 2nd cycle. Score performance of appropriate body languade as a eye contact indicator are 0% on pracycle; 18,18% on 1st cycle; and 63,64% on 2nd cycle. Score performance of hearing all of students opinion indicator are 0% on pracycle; 48,48% on 1st cycle; and 63,64% on 2nd cycle. Score performance of give a responses with a language and body about others opinion indicator are 0% on pracycle; 39,39% on 1st cycle; and 63,64% on 2nd cycle. The conclusion of the research showed that there was enhancement of the students oral communication skills through the implementation of Problem Based Instruction learning model. Keywords : oral communication skills, problem based instruction